2003
DOI: 10.1002/mame.200390023
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Soft Segment Length and Chain Extender Structure on Phase Separation and Morphology in Poly(urethane urea)s

Abstract: The phase separation and morphology in poly(urethane urea)s were investigated as soft segment length and chain extender structure were varied. Increases in soft segment length led to increased phase separation that resulted in greater mobility of the soft segment. This was shown by lower soft segment glass transition temperatures in differential scanning calorimetry (DSC) as well as a shift of Emax″ and tan δmax to lower temperatures. Also the structure of the chain extender affected the degree of phase separa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 39 publications
1
47
0
Order By: Relevance
“…Many researchers 31,[34][35][36][37][38] assigned the bright region to hard blocks and dark region to soft blocks. However, Magonov et al 39 observed contrast inversion in phase images by reducing r sp .…”
Section: Synthesis Of Fpcusmentioning
confidence: 99%
“…Many researchers 31,[34][35][36][37][38] assigned the bright region to hard blocks and dark region to soft blocks. However, Magonov et al 39 observed contrast inversion in phase images by reducing r sp .…”
Section: Synthesis Of Fpcusmentioning
confidence: 99%
“…This is mainly due to a restricted mobility of the soft segments for short molecular chains. 11 As the temperature is raised, an exothermic peak appears at about 0-5 o C for the block copolymers with the MW of PEG lower than 2,000. This transition is generally referred to "cold crystallization" of the soft segments, which is a result of the rearrangement and ordering of nearby segments in the amorphous regions of the PUs.…”
Section: Resultsmentioning
confidence: 97%
“…[6][7][8][9][10] The microphase separation of PUs is greatly influenced by the miscibility of the starting compounds, the structure and the molar mass distribution of the segments, the average block lengths, and the ratio of hard to soft segments. 11 Many methods, for example, polarized optical microscope (POM), scanning electron microscope (SEM), dynamic mechanical analysis (DMA), small angle X-ray scattering (SAXS), [12][13][14][15][16] atomic force microscopy (AFM), 11,17 differential scanning calorimetry (DSC), 18 Fourier transform infrared spectra (FTIR) 19 and nuclear magnetic resonance (NMR) 20 etc., have been used to probe the microphase separation. Since the microphase separation and the phase morphology have an important influence on the ultimate properties of the PU copolymers, it is desirable to have a control on the microphase separation in PUs.…”
Section: Introductionmentioning
confidence: 99%
“…PURs prepared from MDI, 1,3 -PDA, and a poly(caprolactone) diol of a M n molecular weight of 530 have been found suitable since they exhibit high tensile strength, a high modulus, and retention of mechanical properties when degraded adequately to the time required for the application [16,44]. (ii) Meniscal and fi brocartilage reconstruction.…”
Section: Musculoskeletal Applicationsmentioning
confidence: 99%